The role of money in monetary policy at the lower bound - Roberto M. Billi; Ulf Söderström; Carl E. Walsh (Sveriges Riksbank, 2020)
In light of the current low-interest-rate environment, we reconsider the merit of a money growth target (MGT) relative to a conventional in‡ation targeting (IT) regime, and to the notion of price level targeting (PLT). Through the lens of a New Keynesian model, and accounting for a zero lower bound (ZLB) constraint on the nominal interest rate, we show, not surprisingly, that PLT performs best in terms of social welfare. However, the ranking between IT and MGT is not a foregone conclusion. In particular, although MGT makes monetary policy vulnerable to money demand shocks, it contributes to achieving price level stability and reduces the incidence and severity of the ZLB relative to both IT and PLT. We also show that MGT lessens the need for the fiscal authority to engage alongside the central bank in fighting recessions. To illustrate this fiscal benefit of MGT, we introduce a simple rule for the fiscal authority to raise government purchases when GDP falls below potential. If the government fails to make up for a substantial share of the shortfalls in GDP, then IT performs worse than MGT from the perspective of society.
Keywords: E31; E42; E52; 330; Friedman's k-percent rule; ZLB constraint; fiscal policy; automatic stabilizers